Depression among pregnant women: A hospital based study - Shrestha, Dipty (Journal of Kathmandu Medical College, 2017)
Background: Being a mother for every woman is of great pride. But this moment of happiness and pride is associated with depression that might affect the health of both the mother and the baby. So this matter has to be looked into and taken care of but is not being done especially in our context. Objective: To identify the prevalence of depression and its severity in pregnant women from 14 weeks to 36 weeks of gestation at Kathmandu Medical College and Teaching Hospital. Methods: This is a descriptive and prospective study where 195 pregnant women from 14 weeks to 36 weeks of gestation were enrolled. The study was conducted at Kathmandu Medical College and Teaching Hospital from 1st October 2015 to 1st February 2016. The Centre For Epidemiologic Studies Depression Scale was used in this study to identify depression in pregnancy. This is a structured scale used worldwide to study the relationship between depression and pregnancy. It consists of 20 items; each given a score of 0, 1,2 and 3. A total score of 16 or more is considered depression. After taking informed consent, cases fulfilling the inclusion criteria were asked questions as per the scale and scoring were done. Results: Among the total 195 cases, eight (4.1%) had CESD scale scoring above 16 indicating depression and among these eight cases, five were in the age group of 18 – 25 years, two in the age group of 26 – 30 years and one in the age group of more than 30 years. Conclusion: This study did not show definite relationship between depression and pregnancy. Journal of Kathmandu Medical College Vol. 5, No. 2, Issue 16, Apr.-Jun., 2016